Diagnostic value of real-time four-dimensional transesophageal echocardiography on the implant-related thrombus - Yu, Yi; Zhang, Rui; Chen, Yu-Han; Wang, Ting; Tang, Xiao-Li; Gong, Chang-qi; Shao, Yun; Wang, Zheng; Wang, Yue-Peng; Li, Yi-Gang (Frontiers in Cardiovascular Medicine, 2023)
Objectives This study aims to evaluate the diagnostic value of real-time four-dimensional transesophageal echocardiography (RT4D-TEE) for implant-related thrombus (IRT). Methods We collected 1,125 patients with atrial fibrillation from May 2019 to February 2022 in our hospital. All patients accepted transesophageal echocardiography (TEE) examination to exclude any thrombi before the LAAC procedure. Results There were 760 patients with LAAC, 66 patients with CIED, and 299 patients without any implantations. A total of 40 patients with an established diagnosis of IRT were further analyzed. The accurate detection rate of IRT by RT4D-TEE was 4.8% (40/826), which was higher than 3.8% (31/826) by 2D-TEE (P = 0.004). No IRT was found on TEE in the rest of the 786 patients. These 40 patients were divided into LAAC (n = 23) and CIED (n = 17) groups according to the results of RT4D-TEE. In the LAAC group, IRT distributed on different parts of the LAA occluder surface, 91.3% (21/23) with clumps of thrombi, and 8.7% (2/23) with a thin layer of thrombi covering the surface of the occluder. In the CIED group, thrombi were seen attached to the leads in the right atrium and right ventricle. The thrombi were beaded in 17.6% (3/17), corded in 17.6% (3/17), and clotted in the remaining 64.7% (11/17) of cases. After adjusting the anticoagulant dosage and following up for 6 months, 20% (8/40) of cases were successfully resolved, 67.5% (27/40) became smaller, and 12.5% (5/40) showed no changes. Conclusion The accurate detection rate of IRT by RT4D-TEE was significantly higher than that by 2D-TEE. 2D-TEE has limitations, but RT4D-TEE can be used as an effective complementary method. Imaging and some clinical features differ significantly between IRT on occluder and IRT on CIED lead.